Re-examining the premise of isobaric collisions and a novel method to measure the chiral magnetic effect - Xu, Hao-jie; Zhao, Jie; Wang, Xiaobao; Li, Hanlin; Lin, Zi-Wei; Shen, Caiwan; Wang, Fuqiang (My University, 2019)
In these proceedings we show that the premise of the isobaric and collisions to search for the chiral magnetic effect (CME) may not hold as originally anticipated due to large uncertainties in the isobaric nuclear structures. We demonstrate this using Woods-Saxon densities and the proton and neutron densities calculated by the density functional theory. Furthermore, a novel method is proposed to gauge background and possible CME contributions in the same system, intrinsically better than the isobaric collisions of two different systems. We illustrate the method with Monte Carlo Glauber and AMPT (A Multi-Phase Transport) simulations.
Keywords: chiral magnetic effect; isobaric collisions; density functional theory